Primate Lentiviruses Modulate NF-κB Activity by Multiple Mechanisms to Fine-Tune Viral and Cellular Gene Expression - Heusinger, Elena; Kirchhoff, Frank (Frontiers in Microbiology, 2017)
The transcription factor NF-κB plays a complex role during the replication of primate lentiviruses. On the one hand, NF-κB is essential for induction of efficient proviral gene expression. On the other hand, this transcription factor contributes to the innate immune response and induces expression of numerous cellular antiviral genes. Recent data suggest that primate lentiviruses cope with this challenge by boosting NF-κB activity early during the replication cycle to initiate Tat-driven viral transcription and suppressing it at later stages to minimize antiviral gene expression. Human and simian immunodeficiency viruses (HIV and SIV, respectively) initially exploit their accessory Nef protein to increase the responsiveness of infected CD4+ T cells to stimulation. Increased NF-κB activity initiates Tat expression and productive replication. These events happen quickly after infection since Nef is rapidly expressed at high levels. Later during infection, Nef proteins of HIV-2 and most SIVs exert a very different effect: by down-modulating the CD3 receptor, an essential factor for T cell receptor (TCR) signaling, they prevent stimulation of CD4+ T cells via antigen-presenting cells and hence suppress further induction of NF-κB and an effective antiviral immune response. Efficient LTR-driven viral transcription is maintained because it is largely independent of NF-κB in the presence of Tat. In contrast, HIV-1 and its simian precursors have lost the CD3 down-modulation function of Nef and use the late viral protein U (Vpu) to inhibit NF-κB activity by suppressing its nuclear translocation. In this review, we discuss how HIV-1 and other primate lentiviruses might balance viral and antiviral gene expression through a tight temporal regulation of NF-κB activity throughout their replication cycle.